EFFECT OF RECOMBINANT BOVINE SOMATOTROPIN ON MILK PRODUCTION AND COMPOSITION OF LACTATING BEETAL GOATS - Qudus; M. A.; N. Ahmad; K. Javed; M. Abdullah; M. A. Jabbar; M. O. Omer; Z. M. Iqbal; I. Ahmad (Journal of Animal and Plant Sciences, 2013)
The present study was designed to determine the effect of recombinant bovine somatotropin (rbST) on milk production, composition, and weight gain and biochemical parameters in lactating Beetal goats. Fifteen goats were divided into three group’s comprising A, B & C with five animals in each group according to the lactation stage, parity and milk yield. Group A was used as control, while B & C were subcutaneously injected with 50 & 100 mg /week of rbST for 8 weeks. The treatment of goats with rbST rapidly increased milk yield after the onset of treatment. The highest increase in milk production (29%) was observed in group C that was treated with 100 mg rbST/week while the lowest value was observed in the group A (control). Mild increase in milk protein, lactose, ash, total solids and fat was observed in rbST treated groups On the basis of above mentioned findings it is concluded that 50 mg/wk dose of rbSt is efficacious in increasing milk yield without any adverse effect onhealth of lactating Beetal goats.
Keywords: Recombinant Bovine Somatotropin; Milk Production; Beetal Goats; Milk Composition.